Differences in severity of diffuse and focal coronary stenosis between visual and quantitative assessment - Wang, Xinmao; Song, Chao; Liu, Heng; Zhou, Lin; Zhang, Letian (Frontiers in Cardiovascular Medicine, 2024)
BackgroundCoronary Artery Disease (CAD) is a leading cause of mortality, with an increasing number of patients affected by coronary artery stenosis each year. Coronary angiography (CAG) is commonly employed as the definitive diagnostic tool for identifying coronary artery stenosis. Physician Visual Assessment (PVA) is often used as the primary method to determine the need for further intervention, but its subjective nature poses challenges. This study sought to evaluate the differences of severity of diffuse and focal coronary stenosis between PVA and Quantitative Coronary Angiography (QCA).Methods293 patients with coronary artery disease (334 coronary lesions) underwent CAG and fractional flow reserve (FFR). PVA and QCA was used to quantify diameter stenosis (DS). DS ≥50% was defined as obstructive. FFR ≤0.8 was defined as myocardial ischemia.ResultsThe mean ± SD age of all patients was 66 ± 9 years. ΔDS between PVA and QCA was higher in diffuse lesions (16.45 ± 7.37%) than in focal lesions (14.39 ± 7.83%) (P = 0.04). DSPVA and DSQCA had linear negative correlation (rPVA = −0.3182, rQCA = −0.4054) with FFR in diffuse, while in focal, DSPVA and DSQCA had an even stronger linear negative correlation (rPVA = −0.4090, rQCA = −0.4861) with FFR. ROC analysis demonstrated that DSQCA had better discrimination capability for myocardial ischemia (FFR ≤ 0.80) than DSPVA in different of length stenosis.ConclusionsPVA was more likely to overestimate diameter stenosis in coronary arteries than QCA, and the severity of diffuse stenosis was more likely to be overestimated than that of focal stenosis.